2014
DOI: 10.2172/1220504
|View full text |Cite
|
Sign up to set email alerts
|

SSL Adoption by Museums: Survey Results, Analysis, and Recommendations

Abstract: This document is a report of observations and results obtained from a lighting evaluation project conducted under the U.S. Department of Energy (DOE) GATEWAY Program. The program supports evaluations and demonstrations of high-performance solid-state lighting (SSL) products in order to develop empirical data and experience with in-the-field applications of this advanced lighting technology. The DOE GATEWAY Program focuses on providing a source of independent, third-party data for use in decision-making by ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The first step in designing the survey was to search and identify in the literature other relevant questionnaires regarding the sustainable development of museums. Thus, we noticed that previous research focused on assessing museum effectiveness and performance [58], improving energy efficiency [59], identifying sustainability initiatives and measures adopted by museums [60], and evaluating the satisfaction of museum visitors [61]. Although those studies include some economic, environmental, and social sustainability issues, none of them cover all four dimensions of sustainability, and the cultural pillar is almost absent within them.…”
Section: Survey Structurementioning
confidence: 99%
“…The first step in designing the survey was to search and identify in the literature other relevant questionnaires regarding the sustainable development of museums. Thus, we noticed that previous research focused on assessing museum effectiveness and performance [58], improving energy efficiency [59], identifying sustainability initiatives and measures adopted by museums [60], and evaluating the satisfaction of museum visitors [61]. Although those studies include some economic, environmental, and social sustainability issues, none of them cover all four dimensions of sustainability, and the cultural pillar is almost absent within them.…”
Section: Survey Structurementioning
confidence: 99%
“…Moreover, purplepumped LEDs do not exhibit a higher risk than typical incandescent lamp or UV-cut halgon lamp (HA lamp). 13 Ishii et al evaluated the colour degradation of natural dyes and BWS using white LEDs and fluorescent lamps and reported that all white LEDs exhibited lower fading rates compared with a fluorescent lamp by checking BWS #1. 14 Piccablottoa et al evaluated the colour degradation and fading produced by white LEDs with different colour temperatures and a traditional HA lamp.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies are carried out in the field of lighting, specifically museum lighting that indicates the importance of lighting issues beyond other related research (Xu et al , 2017; Garside et al , 2017; Sharif-askari and Abu-hijleh, 2018; Bonomolo et al , 2017; Kramer et al , 2016; Perrin et al , 2014; Druzik and Michalski, 2012; Pedro et al , 2013; Leccese et al , 2018). Among the most critical factors addressed, such as damaging effects of illumination on the artwork, introducing new methods to improve quality and energy consumption are also crucial elements which need to be considered.…”
Section: Past Studiesmentioning
confidence: 99%
“…Perrin et al (2014) provided a report regarding solid-state lighting (SSL) in museums. Compared to Bonomolo's research which studied the lighting system in educational places, this report contains necessary information about conservation science in museum lighting mainly based on questionnaires and expert knowledge.…”
Section: Past Studiesmentioning
confidence: 99%